Phenomenon of transsexual behaviour among youth in Kuala Lumpur: a case study - Rosnon, Mohd Roslan; Dahamat Azam, Mohamad Naqiuddin; Daud, Mohd Najmi (Universiti Putra Malaysia Press, 2013)
Understanding the complex lives of transsexual groups is essential in order to resolve this issue in a more intellectual, systematic and effective manner. Thus, this case study was aimed at knowing more about male-to-female transsexuals, especially among youth, by studying their sexual orientation as well as how far a sense of femininity is felt by them. Eight transsexual women were the informants recruited for this study based on snowball sampling technique. Each informant had completed a semi-structured interview at least twice. The basis of the interview was the principle of saturation in which the informants had been interviewed until no new ideas were emerging. The interview was audio-taped, transcribed verbatim and checked for content based on thematic analysis technique. The findings revealed two important themes from the narrative of the informants, namely, their gender identification and sexual orientation. In terms of gender identification, it was found that all the informants identified themselves according to feminine features although the features did not match their own physical features. Meanwhile, in terms of sexual orientation, the results showed that this group of transsexuals preferred to engage in sexual activities. For them, sexual satisfaction was only achievable by engaging in such sexual activities because of their sexual instinct, which was similar to that of women. One implication of this feature would be a potential rise in social problems. Thus, all parties should cooperate to combat this issue aggressively and effectively.